ANALISIS FAKTOR PENGHAMBAT PEMBAYARAN PAJAK BUMI (PBB) DAN BANGUNAN OLEH MASYARAKAT PEDESAAN DI INDONESIA SAAT INI - Asyami Ramadhani; Dini Vientiany; Muthia Zahra Damanik (INTERNATIONAL, Journal of Sharia Business Management, 2026)
This research aims to analyze the factors inhibiting the payment of Land and Building Tax (PBB) by rural communities in Indonesia today. The method used is a qualitative approach with a descriptive research type through literature study from various relevant scientific journals. The results show that there are two main groups of inhibiting factors, namely internal and external factors. Internal factors include low tax literacy, unstable economic conditions, and negative perceptions of tax benefits. Meanwhile, external factors include weak administrative systems, limited services, lack of socialization, and payment procedures that are considered complicated by the community. These findings indicate that low taxpayer compliance is not only influenced by individual awareness but also by the system and policies implemented by the government. Therefore, strategic efforts are needed such as improving tax education, digitalizing services, and applying social approaches involving the community directly. Thus, it is expected that PBB payment compliance can increase and contribute to optimizing regional tax revenue sustainably.